2019
DOI: 10.1016/j.msec.2018.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles as an effective disinfectant: A review

Abstract: A B S T R A C TThe paradigm modifications in the metallic crystals from bulky to micro-size to nano-scale have resulted in excellent and amazing properties; which have been the remarkable interests in a wider range of applications. Particularly, Ag NPs have much attention owing to their distinctive optical, chemical, electrical and catalytic properties that can be tuned with surface nature, size, shapes, etc. and hence these crystals have been used in various fields such as catalysis, sensor, electronic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
330
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(334 citation statements)
references
References 99 publications
0
330
0
4
Order By: Relevance
“…Currently, the most common nanomaterials include silver, fullerene and carbon nanotubes, zinc oxide, silica and titanium dioxide [6]. For example, Ag NP-based disinfectants have attracted much attention due to their practical applications in daily life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most common nanomaterials include silver, fullerene and carbon nanotubes, zinc oxide, silica and titanium dioxide [6]. For example, Ag NP-based disinfectants have attracted much attention due to their practical applications in daily life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Only one article was found, in which Najafi-Taher et al in 2018 reported a combination method of silver nanoparticleloaded tea tree oil nanoemulsion that showed a good antibacterial effect against E. coli and S. aureus [17]. Meanwhile, nanosilver is a material with a very large surface area, has the following unique characteristics such as disinfection, anti-fungus, deodorization, unharmful to human health at relatively high doses, ability to disperse stably in various solvents, high chemical stability, almost unchanged under the action of light and conventional oxidation-reduction agents [18].…”
Section: ■ Introductionmentioning
confidence: 99%
“…These particles became one of the phenomena of nanotechnology. Recently, more and more products of everyday usage involve these particles, which are applied with respect to their high antibacterial activity against most of the pathogenic bacteria, fungi, and candida [26][27][28]. As the metal nanoparticles represent a material, which is of high importance, from the research and application point of view, this chapter will be devoted to the methods of their tailored preparation via wet chemical reduction methods.…”
Section: Introductionmentioning
confidence: 99%